Selection of the patient for liver surgery major: absolute contraindications and relative. Preoperative factors - Secondo, Gerardo (Cirugía del Uruguay, 2002)
500 years ago Leonardo da Vinci wrote that the liver is the distributor and administrator of vital food for man. More than 500 functions have been found since in the nineteenth century Claude Bemard demonstrated his ability to synthesize glycogen from food, standing out control of carbohydrate metabolism carbon, protein, fat, storage vitamins, plasma protein production and coagulation factors, being the organ that includes most of the reticuloendothelial system